PENGARUH PUPUK ORGANIK SUPERNASA PADA BERBAGAI DOSIS DAN FREKWENSI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT - Sutoyo Sutoyo; Fauzia Hulopi (BUANA SAINS, 2009)
Organic manure of pregnant Supernasa of macro, micro nutriens and hormone grow able to be utilized by tomato crop to race growth process and result. Research aimed to study and knowing organic manure dose of Supernasa at various giving frequency on the growth and result crop tomato. The experiment used split plot design with 3 replications. Giving frequency (1, 2, 3 times) as main plots and dose fertilize Supernasa (1, 2, 3 g/l water) as sub plots. Variables observed to highly plants, leaves number, internode number, fruit number/plant and total fruit weight/plant. Result of research indicate that do not there are real interaction between treatment of dose fertilize Supernasa and giving frequincy to all variable observed. But analyse separately from each treatment indicate that treatment of dose fertilize Supernasa 1 g/l water can yield optimum result and growth so also at 1 times giving frequency, this matter is anticipated by manure of Supernasa represent dissolve solid organic manure old ones and availibility of required by nutrien is plant during which old relative